2017
DOI: 10.1021/acs.inorgchem.7b02405
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Tetrabutano- and Tetrabenzotetraarylporphyrin Complexes: Effect of Substituents on the Electrochemical Properties and Catalytic Activity of Oxygen Reduction Reactions

Abstract: Three series of cobalt tetraarylporphyrins were synthesized and characterized by electrochemistry and spectroelectrochemistry. The investigated compounds have the general formula (TpYPP)Co, butano(TpYPP)Co, and benzo(TpYPP)Co, where TpYPP represents the dianion of the meso-substituted porphyrin, Y is a CH, H, or Cl substituent on the para position of the four phenyl rings, and butano and benzo are respectively the β- and β'-substituted groups on the four pyrrole rings of the compound. Each porphyrin undergoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 66 publications
3
49
0
Order By: Relevance
“…8D and Table 2, row 4). 37,38 However, when stabilisation of this intermediate via H-bonding or bonding with a distal metal atom is included along with the ET site (e.g. FeFc 4 and FeCu-phenol) there is a distinct improvement in selectivity ( Fig.…”
Section: Memarg and Phmarg (Details In The Esi †) In Cdcl 3 Showmentioning
confidence: 99%
“…8D and Table 2, row 4). 37,38 However, when stabilisation of this intermediate via H-bonding or bonding with a distal metal atom is included along with the ET site (e.g. FeFc 4 and FeCu-phenol) there is a distinct improvement in selectivity ( Fig.…”
Section: Memarg and Phmarg (Details In The Esi †) In Cdcl 3 Showmentioning
confidence: 99%
“…4, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition to biologically relevant Fe porphyrins, Co porphyrins have also received great attention because of their high activity and stability. [19][20][21][22][23][24][25][26][32][33][34] However, mononuclear Co porphyrins are much less selective than Fe analogues to catalyze the 4e reduction of O 2 to water. Unlike Fe complexes, Co complexes in general catalyze the 2e reduction of O 2 because the peroxo intermediates of Co are challenging to undergo heterolytic O-O bond cleavage to generate terminal Co-oxo species that have large d electron counts and thus are high in energy.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Several molecular design strategies have been reported to improve the selectivity for the 4e ORR, including (1) formation of intramolecular hydrogen bonding interactions to stabilize O 2 adducts, 27,30,38,39 (2) appending acid groups to assist proton delivery, 19,28,29,40 and (3) introduction of functional groups to ensure rapid electron transfer between catalyst molecules and electrodes. 34,[41][42][43][44] Additionally, for complexes of late-transition metals, such as Co, it is found that dinuclear complexes are typically more efficient than mononuclear analogues to catalyze the 4e reduction of O 2 . [20][21][22][23][24][25][26][45][46][47][48][49][50][51][52][53] This improvement is likely caused by the formation of peroxo-bridged dinuclear intermediates, 45,47 whose subsequent reduction can result in the 4e ORR.…”
Section: Introductionmentioning
confidence: 99%
“…The ORR catalyzed at electrodes modified with CoN4 complexes is of major interest because of the ease and the convenience of the synthesis of those redox complexes and because of the different catalytic properties of the various complexes which were synthetized to optimize the catalysis. For example ORR catalyzed by unsubstituted CoPc or by CoPc with the addition of one or more electron-donating or electronwithdrawing substituents adsorbed directly on graphite proceeds via a 2-electron transfer process (Zagal et al, 1992;Sun et al, 2014;Zagal and Koper, 2016;Ye et al, 2017;Abarca et al, 2019) whereas complexes with pendant residues that increase the electron back-bonding would promote a direct 4-e process as in Equation 2 (Steiger and Anson, 1995;Tse et al, 1997;Riquelme et al, 2018a,b). Co-cofacial bimetallic complexes and dimeric Co porphyrins that bind simultaneously both dioxygen atoms would also transfer directly 4 electrons to O 2 (Collman et al, 1980;Durand et al, 1983;Le Mest et al, 1997;Peljo et al, 2012;Swavey and Eder, 2013;Wada et al, 2013;Dey et al, 2017;Oldacre et al, 2018).…”
Section: Introductionmentioning
confidence: 99%